Televizija v Sloveniji pred uradnim začetkom - Zajc, Melita (Javnost (Ljubljana), 2008)
In 2008, the Slovenian public Radio and Television (RTV Slovenia) is celebrating the 50th anniversary of television, but television in Slovenia began long before 1958. In August 1956 the employees of Radio Ljubljana were already producing TV shows, but television began even earlier. In 1947 the Laboratory for Television was founded in Ljubljana with the aim to develop television equipment. In 1954, the Laboratory also presented a plan to start television broadcasting and organised the first public demonstration of television as a new medium. However, much earlier - in 1929 - baron Anton Codelli of Ljubljana succeeded to transmit mechanically an image at a distance. The multiplicity of "the firsts" clearly demands some cautiousness in defining "the beginnings." The reconstruction of some phenomena from the early history of television in Slovenia also indicates the importance of the conception of technology as a use for contemporary media research. The medium as we know it is only a dominant use of media technology but not the only possible one. It prevailed gradually and not without complications which testify that the relationship between societies and technologies is not a simple cause-effect relation. Development of media technologies is not determined in advance, it depends on debates about the scope and form of social life that involve all members of society. The look into the past is thus also the guidance for the future. How the media of the future are going to be, depends on every one of us.
Keywords: Slovenia; Slovenija; television; televizija; technology; tehnologija; razvoj; tehnološki razvoj